EXPRESSION OF TH17-LYMPHOCYTE ADAPTER – TRAF3IP2 IN THE SKIN OF PSORIASIS PATIENTS - V. R. Khairutdinov (SPb RAACI, 2014)
Abstract. TRAF3IP2 gene plays an important role in the processes of inflammation and autoimmune control. TRAF3IP2 protein acts as a signal transducer from membrane receptors to the cell nucleus and is essential for the biological effects of Th17-lymphocytes. The goal of present study was to investigate distribution of allelic variants of TRAF3IP2 Arg74Trp polymorphism as a risk factor in psoriasis development, and to evaluate TRAF3IP2  mRNA  expression  levels  in  psoriasis  patients  and  healthy  donors.  Peripheral  blood  leukocytes were used as a source of DNA. Gene testing was performed for 261 patients and 482 healthy blood donors by real-time allele-specific PCR. TRAF3IP2 mRNA expression was measured in the skin biopsy samples from 36 patients with psoriasis and 14 healthy donors by means of quantitative reverse transcriptase PCR, using a paired-sample approach with SDHA reference gene. We have observed a significantly increased occurrence of rare Trp allele, with 10.5% among psoriasis patients (55/522), as compared with 7.0% (67/964) for healthy persons (OR = 1.58, 95% CI: 1.09 – 2.28, р = 0.02). A trend of higher Trp allele occurrence was revealed in patients with severe psoriasis – 21/154 (13.6%) when compared to the patients with milder course of the disease – 34/368 (9.2%) (р = 0.14). No differences were found for TRAF3IP2 mRNA expression in skin samples from psoriasis patients versus healthy persons. The association between TRAF3IP2 Trp allele and increased susceptibility to psoriasis suggests that Trp variant of this protein may display a higher enzymatic activity. Induction of inflammatory process in carriers of Trp allele would be more intensive, thus being a predisposing factor in psoriasis development. (Med. Immunol., 2011, vol. 13, N 6, pp 597-602)